Effect of processing parameters on electroless Cu seed layer properties - Chen, Z. (2012)
Electroless Cu seed layer is essential for subsequent copper metallization by electroplating for sub-micron wafer technology. This layer is required to provide good step coverage and high uniformity. In the current work, electroless copper was deposited on a TiN surface activated by palladium. The effect of deposition time on the properties of electroless Cu films was reported. It shows that as the deposition time increases, the surface coverage of Cu film on activated TiN is improved and there is a significant reduction in sheet resistance and an increase in grain size of deposited copper film. Of particular interest is that there exists a preferred Cu (111) crystal orientation in the samples subjected to more than as short as 3 min of deposition. A surface roughness (Rrms) of ∼17 nm has been achieved. The results obtained in current study points out a promising process for laying down thin Cu seed layer.